A new class of oxidosqualene cyclases directs synthesis of antimicrobial phytoprotectants in monocots - Haralampidis, K. (The National Academy of Sciences, 2001)
Many plants synthesize antimicrobial secondary metabolites as part of their normal program of growth and development, often sequestering them in tissues where they may protect against microbial attack. These include glycosylated triterpenoids (saponins), natural products that are exploited by man for a variety of purposes including use as drugs [Hostettmann, K. & Marston, A. (1995) Saponins (Cambridge Univ. Press, Cambridge, U.K.)]. Very little is known about the genes required for the synthesis of this important family of secondary metabolites in plants. Here we show the novel oxidosqualene cyclase AsbAS1 catalyzes the first committed step in the synthesis of antifungal triterpenoid saponins that accumulate in oat roots. We also demonstrate that two sodium azide-generated saponin-deficient mutants of oat, which define the Sad1 genetic complementation group, are defective in the gene encoding this enzyme and provide molecular genetic evidence indicating a direct link between AsbAS1, triterpenoid saponin biosynthesis, and disease resistance. Orthologs of AsbAS1 are absent from modern cereals and may have been lost during selection, raising the possibility that this gene could be exploited to enhance disease resistance in crop plants.